Improving Digital Library Interfaces by Investigating the Electronic Activities of Users - Qayyum, M. Asim (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
The purpose of this study was to examine the navigational patterns and text markings of electronic text readers when they interacted with electronic documents during an active reading process. The readings took place in two settings, private and document sharing, and the results provided us with user-navigational patterns taxonomy. Le but de cette étude était d’examiner les modèles de navigation et de marquage de textes électroniques des lecteurs lorsqu’ils interagissent avec les documents numériques pendant un processus de lecture active. Les séances de lecture ont eu lieu dans deux environnements, à l’aide de documents privés et partagés, et les résultats ont offert une taxinomie sur les modèles de navigation des utilisateurs.